2000
DOI: 10.1074/jbc.m005210200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human α2-Adrenergic Receptors in Adipose Tissue of β3-Adrenergic Receptor-deficient Mice Promotes Diet-induced Obesity

Abstract: Catecholamines play an important role in controlling white adipose tissue function and development. ␤-and ␣2-adrenergic receptors (ARs) couple positively and negatively, respectively, to adenylyl cyclase and are coexpressed in human adipocytes. Previous studies have demonstrated increased adipocyte ␣2/␤-AR balance in obesity, and it has been proposed that increased ␣2-ARs in adipose tissue with or without decreased ␤-ARs may contribute mechanistically to the development of increased fat mass. To critically tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 32 publications
7
78
0
2
Order By: Relevance
“…The functional importance of the marked a2A-AR effect in human cells is not entirely clear but it has been speculated that an increased antilipolytic response to catecholamines may promote fat accumulation in adipocytes. 7 In line with this, previous work has shown that adipocytes from infant subjects display a lower lipolytic capacity than that observed in adipocytes from adults. 8 This may constitute a mechanism that promotes fat cell growth and secures energy storage in the growing fat cell.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The functional importance of the marked a2A-AR effect in human cells is not entirely clear but it has been speculated that an increased antilipolytic response to catecholamines may promote fat accumulation in adipocytes. 7 In line with this, previous work has shown that adipocytes from infant subjects display a lower lipolytic capacity than that observed in adipocytes from adults. 8 This may constitute a mechanism that promotes fat cell growth and secures energy storage in the growing fat cell.…”
Section: Introductionsupporting
confidence: 62%
“…Overexpression of human a2A-AR in mice homozygous for a null mutation in the b3-AR gene promotes high-fat diet obesity, primarily by adipocyte hyperplasia. 7 This would suggest that a2A-AR expression is associated with increased adipocyte proliferation and not hypertrophy. However, several reports have demonstrated that mature fat cells from obese subjects display increased a2A-AR expression, a2A/bÀAR ratios and a2A-AR responsiveness compared to cells from lean subjects [20][21][22][23] This has led to the hypothesis that an enhanced a2A-AR effect is a prerequisite for the well-established obesity-associated fat cell hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data suggest that visceral adipocytes have a smaller death critical size (size-triggering death) (41), in line with the well-known greater morbidity due to accumulation of visceral fat (80). Interestingly, we failed to detect CLS in either mice or humans with hyperplastic obesity, which is characterised by small adipocytes and the absence of secondary metabolic disorders (73,81). The positive correlation between adipocyte size and insulin resistance has recently been confirmed in non-obese humans (82).…”
Section: Figuresupporting
confidence: 53%
“…Mice and human subjects with hyperplastic obesity do not show CLS and are insulin sensitive (63,65) . The adipocytes in the newborn are small and progressively increase in size, because of a progressive increase in their lipid content, until they reach the characteristic size of mature adult cells (54) .…”
Section: The Adipose Organ Renews Its Cellsmentioning
confidence: 97%